2021
DOI: 10.14306/renhyd.25.s1.1272
|View full text |Cite
|
Sign up to set email alerts
|

Diferencias morfológicas y de condición física en futbolistas adolescentes según posición de juego: una revisión sistemática

Abstract: Introducción: El objetivo de la presente revisión sistemática fue analizar los estudios que evalúan las diferencias morfológicas y de condición física en futbolistas adolescentes según posición de juego.Material y métodos: Para su elaboración se siguió el protocolo PRISMA-P, se utilizó la base de datos PubMed/MEDLINE y se aplicó la evaluación de calidad metodológica de Downs & Black. Seis estudios cumplieron con todos los criterios de selección, sumando 784 futbolistas (229 defensas [DF]; 271 mediocampista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…The inclusion criteria for this systematic review were: (i) original articles written in English, Spanish, or Portuguese; (ii) that were published up to January 2024; (iii) that recruited adult individuals aged 18 or over of both sexes; (iv) that included individuals who were overweight and/or obese, according to the definitions presented by the studies based on BMI; (v) that included hospitalized individuals with a confirmed diagnosis of COVID-19 by real-time polymerase chain reaction (real-time PCR); (vi) that presented studies with an experimental design: cross-sectional, retrospective, and/or prospective; (vii) that the object of the study included individuals with overweight and/or obesity as a risk factor for COVID-19 complications; and (viii) studies with 60% or more of the total score when the Downs and Black scale was determined for more considerable reliability of the results [ 23 , 24 ]. On the other hand, the exclusion criteria were: (i) duplicate articles; (ii) case studies; (iii) Mendelian randomization analysis; (iv) studies linking COVID-19 with other underlying diseases (cancer, diabetes mellitus, hepatic steatosis, cardiovascular diseases, polycystic ovary, anorexia, influenza, human immunodeficiency virus, tuberculosis) or with pregnant women; (v) studies with associated interventions (e.g., psychological intervention, bariatric surgery), psychological intervention, bariatric surgery, vaccination, nutritional therapy/support); and (vi) studies with partial data from individuals without COVID-19.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria for this systematic review were: (i) original articles written in English, Spanish, or Portuguese; (ii) that were published up to January 2024; (iii) that recruited adult individuals aged 18 or over of both sexes; (iv) that included individuals who were overweight and/or obese, according to the definitions presented by the studies based on BMI; (v) that included hospitalized individuals with a confirmed diagnosis of COVID-19 by real-time polymerase chain reaction (real-time PCR); (vi) that presented studies with an experimental design: cross-sectional, retrospective, and/or prospective; (vii) that the object of the study included individuals with overweight and/or obesity as a risk factor for COVID-19 complications; and (viii) studies with 60% or more of the total score when the Downs and Black scale was determined for more considerable reliability of the results [ 23 , 24 ]. On the other hand, the exclusion criteria were: (i) duplicate articles; (ii) case studies; (iii) Mendelian randomization analysis; (iv) studies linking COVID-19 with other underlying diseases (cancer, diabetes mellitus, hepatic steatosis, cardiovascular diseases, polycystic ovary, anorexia, influenza, human immunodeficiency virus, tuberculosis) or with pregnant women; (v) studies with associated interventions (e.g., psychological intervention, bariatric surgery), psychological intervention, bariatric surgery, vaccination, nutritional therapy/support); and (vi) studies with partial data from individuals without COVID-19.…”
Section: Methodsmentioning
confidence: 99%
“…The instrument consists of 27 items, relating to reporting (10 items), external validity (3 items), internal validity bias (7 items), internal validity confounding (selection bias) (6 items), and statistical power (1 item), allowing a study to be rated between 0 and 32 points. The complete list is usually applied for randomized studies, whereas for non-randomized studies, it is reduced to 17 criteria after excluding items 9,13,14,17,19,22,23,24,26, and 27, which are not applicable in non-randomized studies, leading to a maximum score of 17 points [26]. In this way, the original non-randomized controlled trials and descriptive studies positively evaluated 60% (10 points or more out of 17) of the criteria selected and included in the subsequent analyses since they presented a moderate to high methodological quality [23,25,26].…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%